Patrones de diversidad genetica en Phaseolus : hechos, ideas e implicaciones - Debouck, Daniel G. (International Center for Tropical Agriculture, 1988)
The concept of plant genetic variability is studied as well as how it should be treated and presented to the researcher, especially in the management of bean genetic resources. Given the spread of some crops such as soybeans and pods, searching for variability in the available genetic resources for bean breeding is proposed, to avoid pressure on the crop as a result of the appearance of new pests or diseases and contribute to producing low- cost plant protein. The bean collection, especially that of wild materials, does not show enough variability, for which measures should be adopted to preserve the current and identify new species as well as their characteristics, geographic distribution, and threats in their habitat. Wild forms allow to specify the geographical origin of the cultivated material through molecular markers such as phaseollin. Bean domestication included only a small fraction of the whole genetic variability; the presence of allogamy in bean species allows for maintaining the wild-weed-crop complex, where in some cases the cultivated material is crossed with the wild material, resulting in weed-type forms that help preserve the variability phenomenon. (CIAT)